The sustainability shift refashioning Malaysia's future - Adnan A. Hezri (Areca Books, 2016)
The Sustainability Shift: Refashioning Malaysia s Future discusses the threats of environmental degradation, climate change and imminent ecological collapse faced by humanity today. These issues demand an urgent response from individuals, industries and national governments. Yet, in most countries, national policies are still based on fragmentary thinking and unsound science. Malaysia, a resource-rich upper-middle income economy, is no exception. It will certainly make a difference globally if Malaysia home to an important tropical rainforest with mega-diverse species richness can make a transition to sustainability. Malaysia faces a spectrum of institutional challenges as it grapples with this transition. Instead of looking at environmental problems through a compartmentalised perspective, it is essential to understand the common root causes of an overarching unsustainability. This book shows how, by reforming its institutional hardware, software and heartware , Malaysia can nurture an inclusive, sustainable society and also benefit economically by greening its growth.